Integrating generative AI in English education opportunities and challenges for EFL learners - Samsudin; Charlie Joseph Allen (Journal of Research in English Language Teaching and Linguistics, 2026)
The growing integration of generative artificial intelligence in English language education has reshaped how learners interact with language, making it a timely and important area of investigation. Recent studies have highlighted the potential of AI to enhance learning through immediate feedback, increased accessibility, and personalized support, while also raising concerns about dependency, reduced critical thinking, and ethical use. Despite these developments, limited attention has been given to how learners themselves interpret both the opportunities and challenges of using generative AI in their everyday learning practices. This study aims to explore EFL learners’ perceptions of generative AI, focusing on both its benefits and its limitations within authentic learning contexts. An interpretive research design was employed to capture learners’ lived experiences. The study involved 20 undergraduate EFL students who had prior experience using generative AI tools in their English learning. Data were collected through semi-structured interviews and reflective journals over a four-week period, allowing for both immediate and reflective insights. The data were analyzed using thematic analysis, involving coding, categorization, and the identification of recurring patterns across participants’ responses. The findings reveal that learners perceive generative AI as a supportive learning partner that enhances confidence, flexibility, and engagement through features such as instant feedback, reduced anxiety, and assistance in vocabulary and idea development. At the same time, learners report significant challenges, including overreliance on AI, reduced critical thinking, superficial understanding, and concerns about inaccurate outputs and ethical use. These findings suggest that generative AI functions as a double-edged tool in language learning. The study highlights the need for guided and reflective use of AI, emphasizing the role of educators in fostering critical awareness and responsible engagement to ensure that technological support leads to meaningful learning outcomes.